"Like a family": Coach perceptions of wheelchair sport in conflict-affected low- and middle-income countries - Kirk, T. N.; McKay, C.; Holland, K. (International Sport Coaching Journal, 2026)
Research suggests that coaches play an important role in facilitating physical, psychological, and social benefits of Parasport participation for disabled athletes. Despite the importance of this role, little is known about the perspectives of Parasport coaches from low- and middle-income countries of ongoing or recent armed conflict in which resources are often scarce. This research explored the experiences and perceptions of wheelchair basketball coaches working in conflict-affected low- and middle-income countries. Ten national-level wheelchair basketball coaches from conflict-affected Middle East and North Africa or South Asia regions participated in semistructured interviews. Study data were analyzed thematically using an interpretive descriptive approach, resulting in three themes. "When I see them improve every day ... I am content," described the personal meaning of coaching. "This ... has changed their life drastically," pertained to coaches` perceptions of the impact of wheelchair basketball participation on their players. Finally, Theme 3, "If your basement is weak, it cannot be the foundation for a two-story building," concerned the need for Parasport resources in conflict-affected low- and middle-income countries. Study findings suggest that while some aspects of the Parasport coaching experience are similar across geographic contexts, additional research and supports are needed to support Parasport development in underresourced contexts.